Religious motivation for mitigating human‐forced climate change: Scientifically informed, politically astute, and collaborative. Issue 1 (2014) - ,
Abstract : Purpose – Religious organizations are among the non‐government groups in the USA that are addressing climate change phenomena from their various faith perspectives and, despite the differences in their traditions and practices, are collaborating with one another to achieve their mutual goal – the establishment of policies that will mitigate the real and anticipated perils scientists are forecasting. If sufficiently motivated by their faith, informed by climate science, and politically astute, these groups may be reliable allies for climate change decision‐makers to tap as they strive to achieve their mutual goal. The paper aims to discuss these issues.Design/methodology/approach – Focusing on the Coalition on Environment and Jewish Life, the Catholic Coalition on Climate Change, and Interfaith Power and Light, the author explores the diverse religious faith‐based motivations underpinning their efforts, the extent to which they remain cognizant of the latest climate science, the structures through which they share their particular faith perspectives and collaborate with one another, and their efforts to reach decision makers at various levels of governance.Findings – Motivated by their religious faiths, these three organizations demonstrate that they are scientifically informed, politically astute, and collaborative with others in striving to achieve their mutual goal of mitigating the adverse effects of climate change locally to globally.Research limitations/implications – The three groups on which the author focuses are based in the USA and collaborate with one another. In an earlier presentation prepared for an international conference, the author included two other groups outside the USA, but manuscript length precluded their inclusion in this submission. Perhaps the author's limited study will stimulate scholars to explore other groups in various parts of the world.Practical implications – To assure and strengthen the momentum already underway, scholars of religions need to probe their foundations for responding to climate change, leaders of religious communities must heighten their efforts to educate their followers accordingly, adherents of religions must be open to embracing their motivating traditions, and religiously based groups must seek to collaborate with one another at various bioregional and political levels to demand actions that will advance a life‐sustaining climate.Originality/value – The author is unaware of studies exploring these three groups using the methodology the author employs for the purposes of describing and assessing the effectiveness of religious groups in addressing human‐forced climate change.